Dekonstruksi Narasi Toxic Relationship di Media Sosial Analisis Hukum Keluarga Islam terhadap Sindrom Fear of Marriage pada Gen Z - Nur Hazmi Asyikin; Rusdaya Basri; Budiman Budiman; Agus Muchsin; Aris Aris (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2026)
This study aims to analyze the phenomenon of toxic relationship narratives on social media and their influence on the emergence of fear of marriage syndrome among Generation Z from the perspective of Islamic family law. The widespread exposure to negative relationship content on digital platforms has shaped collective perceptions that marriage is a source of emotional harm rather than a sacred institution. This research employs a normative legal approach with conceptual and statutory methods, focusing on Islamic legal principles and maqashid sharia. The findings indicate that social media plays a significant role in constructing negative perceptions of marriage, which contradicts Islamic teachings that emphasize sakinah, mawaddah, and rahmah. This study contributes to the discourse by integrating digital media analysis with Islamic family law perspectives, offering a new framework to address contemporary challenges faced by Generation Z.